The impact of investment spending on the gross domestic product in Syria (An analytical study) (Journal of Hama University, 2025)
As a result of the developments that have occurred in the structure of the Syrian economy, and given the importance of investment spending and its role in economic growth and economic development, this research aims to study and analyze the development of investment spending and GDP at constant prices for the year 2000, and on the other hand, to study the impact of investment spending on GDP in Syria during the years of study (2000-2021). Many conclusions were reached, the most important of which are: There is a statistically significant effect of investment spending on the gross domestic product in Syria.